Aedes aegypti dyspepsia encodes a novel member of the SLC16 family of transporters and is critical for reproductive fitness. - Hitoshi Tsujimoto; Michelle A E Anderson; Heather Eggleston; Kevin M Myles; Zach N Adelman (Public Library of Science (PLoS), 2021)
As a key vector for major arthropod-borne viruses (arboviruses) such as dengue, Zika and chikungunya, control of Aedes aegypti represents a major challenge in public health. Bloodmeal acquisition is necessary for the reproduction of vector mosquitoes and pathogen transmission. Blood contains potentially toxic amounts of iron while it provides nutrients for mosquito offspring; disruption of iron homeostasis in the mosquito may therefore lead to novel control strategies. We previously described a potential iron exporter in Ae. aegypti after a targeted functional screen of ZIP (zinc-regulated transporter/Iron-regulated transporter-like) and ZnT (zinc transporter) family genes. In this study, we performed an RNAseq-based screen in an Ae. aegypti cell line cultured under iron-deficient and iron-excess conditions. A subset of differentially expressed genes were analyzed via a cytosolic iron-sensitive dual-luciferase reporter assay with several gene candidates potentially involved in iron transport. In vivo gene silencing resulted in significant reduction of fecundity (egg number) and fertility (hatch rate) for one gene, termed dyspepsia. Silencing of dyspepsia reduced the induction of ferritin expression in the midgut and also resulted in delayed/impaired excretion and digestion. Further characterization of this gene, including a more direct confirmation of its substrate (iron or otherwise), could inform vector control strategies as well as to contribute to the field of metal biology.